Improving product size measurement systems by using piezo-fiber scanner - E. V. Leun (Омский научный вестник)
The article discusses the physical and technical basis for the construction and operation of systems for measuring the size of complex products, taking into account the use of a new spatial light modulator — a piezo-fiber scanner. Its device, operating principle, and main technical characteristics are described. The paper considers the joint operation of a piezo-fiber scanner and a low-coherence interferometer as part of three measurement systems: scanning hybrid 3D measuring heads (MH) with the introduction of an ultra-wide-angle optical system and a corundum tip, as well as two active control devices. It is proposed to use a reference channel for the discussed MH design, and to measure the clearances 1с1 , 1с2 … 1сn when contacting the product arising between the corundum tip and the product near the formed contact zone with the subsequent calculation of the so-called equidistant contours and the final compensation of elastic deformations.